A comparative study of using glibenclamide versus insulin in the treatment of gestational diabetes mellitus and its outcome - Rao, P. S.; Datta, Sujata; Prajwal, S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Gestational diabetes mellitus(GDM) is defined as carbohydrate intolerance of variable severity with onset or first recognition during pregnancy. This study aims at determining the efficacy of the glibenclamide versus insulin in achieving the adequate glycemic control and to analyze the maternal and fetal outcomes and to determine the failure rate of glibenclamide, patient compliance and overall cost of the treatment Methods: This study was carried out for a period of 22 months at Command Hospital Air Force, Bangalore in Dept. of OBG. Women with GDM whose glycemic control was not achieved with medical nutrition therapy with fasting blood sugar (FBS) values >105mg/dl and 2hour post prandial blood sugar (PP) value >140mg/dl were selected and randomized for treatment either glibenclamide or insulin (50 in each group). Results: The age of the patients in this study ranged from 23 to 33 years. The mean age in glibenclamide group was 27.32 (SD ± 2.84) where as in insulin group was 26.30 (SD ± 3.01). The mean plasma glucose level achieved with glibenclamide was fasting -87.62 mg/dl, post prandial -116.44 mg/dl, before lunch - 95.62mg/dl, after lunch -115.80 mg/dl, before dinner-91.96 mg/dl, after dinner - 116.64 mg/dl, 3AM - 84.42 mg/dl and next day fasting - 86.30mg/dl in comparison with insulin where fasting- 85.54 mg/dl , post prandial -114.14 mg/dl, before lunch - 87.08, after lunch -112.82 mg/dl, before dinner-86.76 mg/dl and after dinner - 114.18 mg/dl, 3AM - 81.16 mg/dl and next day fasting was 86.72mg/dl which is statistically significant. The incidence of maternal and neonatal morbidities was comparable in both the group. 4 % percent of patient treated with glibenclamide had treatment failure. The cost of the treatment and compliance was better with glibenclamide. Conclusions: It has been concluded that glibenclamide is effective as insulin in achieving adequate glycemic control with no significant maternal and fetal morbidity and mortality.